Natural deep eutectic solvents in phytonutrient extraction and other applications - Li, Dan (Frontiers in Plant Science, 2022)
Natural deep eutectic solvents (NaDESs) are considered a new type of green solvent with attractive application prospects in many fields because of their simple preparation, low cost, environmental friendliness, low volatility, and high solvency capacity, designable structure, and easy biodegradability. Due to their biocompatibility, they are safe to use and are particularly suitable for natural product applications. In recent years, NaDESs have been used to extract phytonutrients (e.g., flavonoids, saponins, polysaccharides, alkaloids, quinones, phenolic acids, volatile oils, etc.) to improve their solubility, stability, and bioavailability. This review is intended to summarize and discuss recent progresses in the field of natural products related to the materials and preparation methods, physicochemical properties, enhancing extraction and separation, increasing solubility, improving stability and bioavailability, and facilitating oral absorption of phytonutrients, and. Finally, highligting the challenge for future work.